Consumers’ Confidence in Halal Labeled Manufactured Food in Malaysia - Rezai, Golnaz (2008)
The impending international challenges facing Malaysia will continue to be dominant and will affect its economic prospects considerably. With an increasing trend towards globalization, Malaysia will face sweeping technological changes in food manufacturing which require re-examining strategies of conducting their businesses. Currently, the key areas for growth and development in the food processing industry in Malaysia are functional and convenience foods, food ingredients and halal foods. Today, halal stands not only for the way of slaughter and preparation of food but also for animal welfare, social justice and sustainable environment. The lack of enforcement in monitoring the usage of certified halal food has caused the public to question the validity of some of the products that were claimed to be halal. The objective of this study is to gather information on consumers’ confidence towards halal labeled food and to assess the level of confidence of the halalness of food products which carry halal logo. This study used data collected from a consumers’ survey via structured questionnaire. Eighteen hundred and sixty (1860) respondents were interviewed in order to obtain their confidence on halal food products. The questions asked included subjects such as confidence, perceptions and attitudes toward halal food, awareness and reasons for using Halal logo. A Likert scale of 1 to 5 (1 representing not confident and 5 representing very much confident) was used to measure consumer’ confidence on the statements formulated in relation to Halal manufactured food products. In this study, the descriptive analysis, chi-square, factor analysis, and binary logistic and multinomial logit method were applied to analyze the data. The findings indicate that the majority of the Muslim consumers are concerned about halal food and the Halal logos on food products. Even though it is shown that consumers react more positively to halal food with local halal logo, there is still enough evidence to support that consumers are more careful in evaluating the halalness of all kinds of food products by referring to the list of ingredients. Nevertheless, most consumers are able to differentiate Malaysian halal logo from others, regardless of the presence of products’ brand on the food packaging. Based on factor analysis, six factors that influenced the purchase of food products on the basis of halal labeling were identified. These factors are; confidence with Halal logo, degree of awareness, trustworthiness, safety and health consciousness, governmental involvement and manufacturing practices. In general, various socio-economic and attitude factors significantly influenced the likelihood of consumers’ confidence on JAKIM halal logo. Apparently, the consumption of halal food for non-Muslims is different from the consumption of halal food for Muslims. The religious concern and safety concepts associated to halal foods probably make this decision more important for the consumers especially Muslims, and thereby lead to different decision-making processes. In addition it can be observed that consumers are very sensitive to halal information and any information or knowledge that might result in loss of their confidence level which might affect their intended purchasing decisions. Misuse, modification or unauthorized access to halal logo on food products can adversely affect an individual’s confident intention and overall business trading. As a matter of fact, Malaysian government, policy makers , food manufacturers and related institutions should fulfil the needs of consumers in order to restore any confidence lost. There should be an efficient coordination throughout all the marketing chain from government to producers in order to offer trustworthy and reliable halal labeled food products.